FINANCIAL MANAGEMENT BEHAVIOR OF PLANTATION FARMER HOUSEHOLDS IN ISLAMIC FINANCIAL MANAGEMENT - Nurbaiti,; Aziz, Imam Abdul (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
This study aims to determine the household financial management of Plantation Farmers in Tanjung Jabung Barat Regency and its conformity with Islamic Financial Management. This research uses two methods, namely descriptive qualitative and quantitative. The data analysis technique used in qualitative methods is descriptive analysis, in collecting data through unstructured interviews. While the data analysis technique used in quantitative methods is Importence Performance Analysis, with data collection techniques using a questionnaire. The sample in this study was the community of Plantation Farmers in West Tanjung Jabung Regency, Jambi. The results of the qualitative descriptive method research show that the household financial management of Farmers is mostly in accordance with Islamic Financial Management, such as doing good and halal work, being wise in consumption, prioritizing needs, recording debts properly and correctly, setting aside income for savings, returning debts in accordance with the agreement, and carrying out zakat infaq and sadaqah. This is reinforced by the results of data analysis using the Importence Performance Analysis method with the results of the level of conformity between expectations and performance of 82. These results indicate that the household financial management of Farmers is at a good level in accordance with Islamic Financial Management.